The Effect Of Market Value Ratio And Activity Ratio On Financial Distress In Technology Sector Companies Listed On The Idx 2021 - 2023 - Cintya Nindy Nofita; Asep Darmansyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Technological developments in Indonesia have encouraged the growth of the technology sector, however the tech winter phenomenon in 2022 caused a decline in investor interest, resulting in funding difficulties and potential financial distress for technology companies. This can be seen from the significant decline in the ROA profitability ratio. The decline in ROA indicates that technology companies are increasingly inefficient in managing assets to generate net profits. This condition has certainly received attention and the author wants to evaluate it in depth to prevent more severe negative impacts in the future. The aim of this research is to examine the influence of Earning Per Share (EPS), Price Book Value (PBV), Total Asset Turnover (TATO), and Fixed Asset Turnover (FATO) on predicting financial distress using the Altman Z-Score model in sector companies technology listed on the Indonesia Stock Exchange (IDX) for the period 2021Q1 to 2023Q2. This research uses 13 samples of technology sector companies listed on the IDX with a study period of 3 years. The company's financial data was analyzed using panel data regression analysis techniques to determine the influence of the independent variables on the dependent variable. The results of this study show that TATO is partially significant and has a positive effect on financial distress. EPS, PBV, FATO are partially not significant effect on financial distress. For EPS, PBV, TATO, FATO simultaneously have a significant effect on financial distress in technology sector companies. The findings of this research are expected to provide valuable insights for investors, creditors and other stakeholders in assessing the financial risks of technology companies and help them reduce the risk of losses